2022
DOI: 10.1136/bcr-2022-250601
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi-Fujimoto disease following SARS-CoV-2 vaccination

Abstract: A previously healthy Japanese woman in her 20s was admitted to our hospital with a 2-week history of fever (39.0°C) and a 1-week history of painful cervical lymphadenopathy. The day before fever onset, she had received her first Pfizer-BioNTech SARS-CoV-2 vaccine in her left arm. She had previously been treated with empirical antibiotics with no improvement. Physical examination revealed painful lymphadenopathy in both posterior cervical regions. CT showed symmetrical lymphadenopathies in the neck, supraclavic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…No restrictions were placed on the year of publication. Only literature published in English was selected, including studies that reported histopathological and/or cytological findings in vaccine‐related lymphadenopathy 17,20,22,23,35–64 . Studies on SLDI, which was generally detected by 18F‐FDG PET‐CT, were also selected and used for the general comprehension and description of the phenomenon and to retrieve cases evaluated by histology or LN‐FNAC 65–68 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…No restrictions were placed on the year of publication. Only literature published in English was selected, including studies that reported histopathological and/or cytological findings in vaccine‐related lymphadenopathy 17,20,22,23,35–64 . Studies on SLDI, which was generally detected by 18F‐FDG PET‐CT, were also selected and used for the general comprehension and description of the phenomenon and to retrieve cases evaluated by histology or LN‐FNAC 65–68 .…”
Section: Methodsmentioning
confidence: 99%
“…While most cases of SLDI do not show clinically evident enlargement of lymph nodes, an awareness of SLDI among doctors is of fundamental importance in a variety of clinical contexts, particularly with regard to cancer staging and follow‐up to avoid the risk of overdiagnosis. In our research, surgical excision or CNB of C19‐LAP‐ or SLDI‐enlarged lymph nodes have been performed in 55 cases 20,22,23,35,39,41–43,47,49–63 . The histological diagnoses were as follows: negative for neoplasia, reactive hyperplasia, and florid reactive hyperplasia (39 cases), 23,39,50–61 progressive transformation of germinal centres (1 case), 54 atypical follicular hyperplasia with light chain‐restricted germinal centres (1 case) 62 granulomatous reaction (2 cases), 50,63 metastases (4 cases), 20,22,50 Kikuchi‐Fujimoto disease (KFD; 6 cases), 40–42,49,56,64 Rosai‐Dorfman‐Destombes disease (RDD; 1 case), 48 and Langerhans cell histiocytosis (LCH; 1 case) 57 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations